2013
DOI: 10.1186/2193-1801-2-533
|View full text |Cite
|
Sign up to set email alerts
|

Use of the kidney injury molecule-1 as a biomarker for early detection of renal tubular dysfunction in a population chronically exposed to cadmium in the environment

Abstract: Cadmium (Cd) has been found as an environmental pollutant in Mae Sot district, Tak province, Thailand. Prolong exposure to high levels of Cd of the resident increases high risk of Cd toxicity especially to kidney which is the primary target of Cd. In order to investigate the early effect of Cd induced renal dysfunction, a kidney injury molecule-1 (KIM-1), a novel biomarker of renal tubular dysfunction, was measured using an enzyme linked immunosorbent assay (ELISA). The method was validated and used to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Chronic KIM-1 induction however, has been shown to be maladaptive and promotes fibrosis (Ferenbach and Bonventre, 2015) and this correlates with the persistent induction and excretion of KIM-1 in variety of inflammatory and fibrotic pathogeneses in the kidney (van Timmeren et al , 2007). In environmental settings, KIM-1 has demonstrated to be more sensitive than N-acetyl-β- d -glucosaminidase and β2 microglobulin for the detection of kidney injury induced by chronic cadmium exposure (Prozialeck et al, 2007; Ruangyuttikarn et al , 2013). We found that KIM-1, among all the biomarkers examined, was most strongly associated with chromium and arsenic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic KIM-1 induction however, has been shown to be maladaptive and promotes fibrosis (Ferenbach and Bonventre, 2015) and this correlates with the persistent induction and excretion of KIM-1 in variety of inflammatory and fibrotic pathogeneses in the kidney (van Timmeren et al , 2007). In environmental settings, KIM-1 has demonstrated to be more sensitive than N-acetyl-β- d -glucosaminidase and β2 microglobulin for the detection of kidney injury induced by chronic cadmium exposure (Prozialeck et al, 2007; Ruangyuttikarn et al , 2013). We found that KIM-1, among all the biomarkers examined, was most strongly associated with chromium and arsenic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, KIM-1 has become one of the key biomarkers for diagnosis, disease activity monitoring and prognosis of acute kidney injury29303132. There is evidence suggesting that KIM-1 can be used for early screening and diagnosis of renal injury induced by cadmium poisoning333435. However, no clinical data is available assessing the correlation of urinary KIM-1 with lead-induced renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects in the polluted area were participants aged ≥ 40 years in the 2007 health survey (participant rate 83.7%) targeted for residents whose urinary Cd levels were ≥5 μg/g Creat in 2004–5 [25,26]. The numbers of subjects in the non-polluted area was small, which is a serious limitation of this study, but addition of these subjects in the non-polluted area increased the low rate of subjects with urinary Cd < 5 μg/g Creat in the polluted area.…”
Section: Methodsmentioning
confidence: 99%